2015
DOI: 10.14712/23361980.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the subsidence based on dInSAR and GPS measurements near Karviná, Czech Republic

Abstract: The main impacts on the landscape due to coal mining in the Czech part of the Upper Silesian basin are ground subsidence and manmade landscape changes related to the mining. Two measurement techniques were used to determine the values of subsidence; these were then compared together to verify the results obtained. The first, differential SAR interferometry (dInSAR), a remote sensing method, was applied by Gamma Remote Sensing in the frame of ESA GMES Project Terrafirma, using ALOS PALSAR data. The second was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…To enrich the research, additional data from the remote sensing method (InSAR) were used (Kadlečík et al, 2015) and the data from the geophysical, geomechanical and classical geodetic monitoring were also implemented (Kajzar, 2018;Kajzar and Doležalová, 2013). However, discussion of these methods goes beyond the scope of this paper.…”
Section: Additional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enrich the research, additional data from the remote sensing method (InSAR) were used (Kadlečík et al, 2015) and the data from the geophysical, geomechanical and classical geodetic monitoring were also implemented (Kajzar, 2018;Kajzar and Doležalová, 2013). However, discussion of these methods goes beyond the scope of this paper.…”
Section: Additional Methodsmentioning
confidence: 99%
“…In this paper, we first summarize the knowledge gained from the evaluation of the surface movements in the Louky locality, partially published, e.g. in Staš et al, 2009;Doležalová et al, 2009;Doležalová et al, 2010;Doležalová, 2011;Kajzar et al, 2011;Doležalová et al, 2012;Kadlečík et al, 2015;Doležalová and Kajzar, 2017;Kajzar, 2018. Then, as a main part of the paper, we extend our analysis to the surface deformations caused by multiple undermining in the area with complex geo-mechanical conditions and classify individual sections of the monitored line structures into building site categories according to the values of horizontal strain, radius of curvature and tilt of the terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Geodetic monitoring of the subsidence trough development is widely applied in the mining areas using GPS, levelling, and total station techniques (e.g. : Jochymczyk, 2005;Blachowski et al, 2009;Doležalová et al, 2009;Bogusz & Mendecki, 2011;Doležalová et al, 2012;Kajzar & Doležalová, 2013;Kadlečík et al, 2015). In recent years, InSAR and PsInSAR studies have also been very popular (e.g., Kadlečík et al, 2010;Mirek & Mirek, 2016;Karakostas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Doležalová et al (2009Doležalová et al ( , 2012 have repeatedly observed subsidence caused by underground coal mining with GPS technique and analysed the time dependence between the mining subsidence and horizontal movements and the progress of exploitation. They have also combined GPS and DInSAR in investigations concerning the Karvina coal basin in the Czech Republic (Kadlečík et al 2015). Samsonov et al (2013) presented a methodology for integration of multiple InSAR data sets for computation of two-dimensional time series of ground deformation and applied it for mapping mining-related subsidence and uplift in the Greater Region of Luxembourg along the French-German border.…”
Section: Introductionmentioning
confidence: 99%